Nanocarbon film with super-continuous gradient structure, and preparation device, method and application thereof

Through centrifugal casting combined with gradient continuous coating, the problem of complex and low efficiency of manufacturing nanocarbon thin films in the prior art is solved, and the supercontinuous gradient structure preparation of nanocarbon thin films is achieved, with simple operation, stable film formation and multiple Advantages of functional applications.

CN119456960APending Publication Date: 2025-02-18SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411663766.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively manufacture nanocarbon films with supercontinuous gradient structures, and faces problems such as complex process, weak interlayer bonding, low efficiency and difficulty in mass production.

Method used

By using centrifugal casting combined with gradient continuous coating, the dispersion of nanocarbon material is continuously sprayed on the surface of the rotating inner cylinder wall and the liquid dispersant is evaporated by heating components to form gradually thickening in the radial direction and components and/or The structure forms a nanocarbon film with gradient changes.

Benefits of technology

It realizes continuous gradient-controlled film formation of two-component nanocarbon materials, which is suitable for the construction of multi-component continuous gradient composite film structures, and provides multi-functional application support for supercontinuous gradient structure composite films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119456960A_ABST
    Figure CN119456960A_ABST
Patent Text Reader

Abstract

The invention discloses a nanocarbon film with a super-continuous gradient structure, and a preparation device, method and application thereof. The method comprises the following steps: rotating the inner cylinder wall to form a centrifugal state; first dispersion liquid and second dispersion liquid are continuously sprayed on the surface of the inner cylinder wall, and the flow of the dispersion liquid continuously changes along with time; and continuous heating is conducted in the non-spraying area, so that the liquid dispersing agent is volatilized, and the nano carbon film which is gradually thickened in the radial direction of the inner cylinder wall and of which the components and / or the structure form gradient changes is formed along with rotating assembly of the inner cylinder wall. The brand-new composite nano carbon film is prepared in the mode that gradient continuous coating is matched with centrifugal casting, operation is easy, film forming is stable, and a new preparation thought is provided for construction of a multi-component continuous gradient composite film structure; the nanocarbon film has excellent electromagnetic shielding performance and low electromagnetic wave reflectivity, and the continuous gradient pore structure of the nanocarbon film plays a crucial role in absorption of electromagnetic waves in a material body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon nanocomposite materials, and in particular to a nano-carbon film with a supercontinuous gradient structure, and a preparation device, method and application thereof. Background Art

[0002] Gradient materials are innovative composite materials characterized by gradual changes in their composition and structure, resulting in tailored properties. Unlike homogeneous materials, gradient materials allow for precise design of their composition and structure, resulting in customizable multifunctional properties. However, traditional methods for manufacturing gradient structures often face challenges such as complex processes, weak interlayer bonding, and low efficiency. In addition, these methods are difficult to scale up or produce continuous gradient changes. Therefore, it is very necessary to develop a universal, economical, and efficient method to mass-produce gradient materials with supercontinuous gradient structures.

[0003] Specifically, researchers have made significant progress in recent years in exploring continuous gradient structures with multifunctional applications. Various materials including metals, ceramics and polymers have been used in the construction of gradient structures, enabling the design of complex structures with customized properties. Notably, nanocarbon-based gradient materials have become the most promising continuous gradient materials due to their superior electrical conductivity, thermal conductivity and mechanical properties. There are several methods to prepare nanocarbon-based gradient materials, such as vacuum filtration, coating and additive manufacturing. By controlling the mass ratio of various nanocarbon materials in a single assembly precursor suspension, the gradient change process can be precisely adjusted to achieve controllable gradient assembly of composite membranes. These films have broad application prospects in electromagnetic interference shielding, thermal management and molecular / ion separation.

[0004] However, the orientation and compact assembly of nanocarbon materials in thin films and the interlayer interfacial bonding of thin films are still limited. In addition, these methods are not suitable for large-scale production because they are time-consuming and complicated procedures, high cost, and have specific requirements for nanocarbon materials and their dispersion. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a nano-carbon film with a supercontinuous gradient structure, a preparation device, a method and an application thereof.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: In a first aspect, the present invention provides a device for preparing a nano-carbon film having a supercontinuum gradient structure, comprising: a first pumping component, a second pumping component, a spraying component, a centrifugal component and a heating component; The first pump assembly is used to pump a first dispersion to the spray assembly, and the second pump assembly is used to pump a second dispersion to the spray assembly, wherein the first dispersion contains a first nano-carbon material, and the second dispersion contains a second nano-carbon material, and the pumping rates of the first pump assembly and / or the second pump assembly can be changed continuously over time; The centrifugal component has a rotating shaft and an inner cylinder wall surrounding the rotating shaft, and can rotate with the rotating shaft as the rotating axis to generate centrifugal force. The spraying component can spray the first dispersion and the second dispersion onto the surface of the inner cylinder wall. The heating component is arranged in cooperation with the centrifugal component to heat the inner cylinder wall.

[0007] In a second aspect, the present invention further provides a method for preparing a nanocarbon film having a supercontinuous gradient structure, comprising: The inner cylinder wall surrounding the rotating shaft is caused to rotate around the rotating shaft to form a centrifugal state; Continuously spraying a first dispersion liquid and a second dispersion liquid on the surface of the inner cylinder wall to form a composite liquid layer, wherein the first dispersion liquid contains a first nano-carbon material, and the second dispersion liquid contains a second nano-carbon material, and the flow rate of the first dispersion liquid and / or the second dispersion liquid changes continuously over time, and the spraying area on the surface of the inner cylinder wall moves in a circumferential cycle due to the rotation of the inner cylinder wall; The composite liquid layer is continuously heated at a position other than the spraying area to volatilize the liquid dispersant, and the nano-carbon film is gradually thickened along the radial direction of the inner cylinder wall and has a gradient change in composition and / or structure as the inner cylinder wall rotates and assembles.

[0008] In a third aspect, the present invention also provides a nano-carbon film obtained by the above preparation method, which comprises at least two nano-carbon materials, and the components and / or structure of the nano-carbon film present a continuous gradient change in the thickness direction.

[0009] In a fourth aspect, the present invention also provides applications of the nano-carbon film in the field of green electromagnetic shielding and Joule heating.

[0010] Based on the above technical solution, compared with the prior art, the beneficial effects of the present invention at least include: The preparation device and method provided by the present invention prepare a new composite nano-carbon film with a supercontinuous gradient structure through gradient continuous coating combined with centrifugal casting. The device and method are simple to operate and have stable film formation. They can well realize the continuous gradient-controlled film formation of two-component nano-carbon materials, provide a new preparation idea for the construction of multi-component continuous gradient composite film structures, and provide support for the multifunctional application of supercontinuous gradient structure composite films.

[0011] The nanocarbon film with a continuous gradient pore structure prepared by the present invention has excellent electromagnetic shielding performance and low electromagnetic wave reflectivity. Its continuous gradient pore structure plays a vital role in the absorption of electromagnetic waves inside the material body, and provides a research basis for the development of nanocarbon materials in the field of green electromagnetic shielding.

[0012] The above description is only an overview of the technical solution of the present invention. In order to enable those skilled in the art to more clearly understand the technical means of the present application and implement them according to the contents of the specification, the following is a description of the preferred embodiments of the present invention in conjunction with detailed drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a structural schematic diagram of a preparation device provided by a typical implementation case of the present invention; Figure 2a This is a macroscopic optical photograph of the RGO surface of the composite nanocarbon film provided by a typical implementation case of the present invention; Figure 2b This is a macroscopic optical photograph of the surface of the composite nanocarbon film SWNTs provided in a typical embodiment of the present invention; Figure 3a This is a scanning electron microscope image of the RGO surface of the composite nanocarbon film provided in a typical embodiment of the present invention; Figure 3b This is a scanning electron microscope image of the SWNTs surface of a composite nanocarbon film provided in a typical embodiment of the present invention; Figure 4a This is a low-magnification scanning electron microscope image of a cross section of a composite nanocarbon film provided in a typical embodiment of the present invention; Figure 4b It is a high-magnification scanning electron microscope image of a cross section of different regions of a composite nano-carbon film provided by a typical embodiment of the present invention; Figure 4c It is a high-magnification scanning electron microscope image of a cross section of different regions of a composite nano-carbon film provided by a typical embodiment of the present invention; Figure 4d It is a high-magnification scanning electron microscope image of a cross section of different regions of a composite nano-carbon film provided by a typical embodiment of the present invention; Figure 4e It is a high-magnification scanning electron microscope image of a cross section of different regions of a composite nano-carbon film provided by a typical embodiment of the present invention; Figure 4f It is a high-magnification scanning electron microscope image of a cross section of different regions of a composite nano-carbon film provided by a typical embodiment of the present invention; Figure 5 This is a mechanical properties test diagram of a composite nano-carbon film provided by a typical implementation case of the present invention; Figure 6aThis is a test diagram of the total electromagnetic shielding effectiveness of a composite nano-carbon film provided by a typical implementation case of the present invention; Figure 6b It is the reflectivity and absorptivity of the composite nano-carbon film incident on different sides of electromagnetic waves provided by a typical embodiment of the present invention; Figure 7 This is a test diagram of the electrical properties of a composite nano-carbon film treated at different temperatures provided by a typical implementation case of the present invention. DETAILED DESCRIPTION

[0014] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle will be further explained as follows.

[0015] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0016] Moreover, relational terms such as “first” and “second” are merely used to distinguish one component or method step from another with the same name, but do not necessarily require or imply any such actual relationship or order between these components or method steps.

[0017] See also Figure 1 As shown, an apparatus for preparing a nano-carbon film with a supercontinuum gradient structure provided by an embodiment of the present invention comprises: a first pumping component, a second pumping component, a spraying component, a centrifugal component and a heating component; the first pumping component is used to pump a first dispersion to the spraying component, and the second pumping component is used to pump a second dispersion to the spraying component, the first dispersion contains a first nano-carbon material, and the second dispersion contains a second nano-carbon material, and the pumping rates of the first pumping component and / or the second pumping component can both change continuously over time; the centrifugal component has a rotating shaft and an inner cylinder wall surrounding the rotating shaft, and can rotate with the rotating shaft as the rotating axis to generate centrifugal force, the spraying component can spray the first dispersion and the second dispersion onto the surface of the inner cylinder wall, and the heating component is arranged in cooperation with the centrifugal component to heat the inner cylinder wall.

[0018] The present invention is based on a method of centrifugal casting and continuous regulation of components to prepare a nanocarbon film with a supercontinuous gradient structure. Centrifugal casting is considered to be a promising and scalable method for manufacturing nanocarbon-based films because it is simple to prepare and has a wide range of uses. It is worth noting that due to the continuous provision of high shear force and high centrifugal force during the synthesis process, this method can produce highly arranged and dense nanocarbon films. However, the traditional centrifugal casting assembly process relies on a uniform precursor suspension to produce a uniform composite film structure. In order to overcome this limitation, the present invention dynamically adjusts the concentration of different components in the precursor suspension during the spraying process to achieve a continuous gradient dense assembly film.

[0019] As for the specific structural form, in some embodiments, the spraying area of ​​the spraying assembly and the heating area of ​​the heating assembly are relatively arranged with the rotating shaft as the center point. The spraying area and the heating area are arranged on two relatively far sides of the circumference, so that there is a certain time interval between the two, providing sufficient time for the diffusion of the material after spraying and the volatilization of the dispersant after heating, which is conducive to the formation of a composite film with a good gradient structure. Of course, in actual work, it is not limited to setting the spraying area and the heating area completely opposite to each other (that is, the line connecting the center points of the two passes through the rotating shaft). A slight offset, such as an angle offset of a certain area within ±45° or ±30° on the circumference is also acceptable.

[0020] In some embodiments, the rotating shaft is arranged non-parallel to the direction of gravity, preferably the rotating shaft is arranged horizontally, the spraying area is arranged at a relatively low position along the direction of gravity, and the heating area is arranged at a relatively high position along the direction of gravity.

[0021] More specifically, in some embodiments, the spraying assembly includes an injection nozzle connected to the first pump liquid assembly and the second pump liquid assembly, the injection nozzle extends into the enclosed space of the inner cylinder wall and points downward to the surface of the inner cylinder wall along the direction of gravity; the heating assembly includes an infrared heater, which extends into the enclosed space and is adjacent to the high area of ​​the inner cylinder wall.

[0022] The preferred implementation case of the present invention arranges the spraying area just below the gravity direction and the heating area just above it, and utilizes the influence of gravity to evenly and vertically spread the atomized dispersion on the surface of the inner cylinder wall. The formed liquid layer is thin and stable, avoiding local liquid phase concentration to form liquid flow and interfere with the film forming process. The thermal effect of the heating component arranged at the top is used to quickly fix the dispersion state in the thin liquid layer, thereby forming a large-area uniform composite film with a distinct gradient structure.

[0023] Correspondingly, an embodiment of the present invention further provides a method for preparing a nano-carbon film having a supercontinuum gradient structure, which is mainly implemented based on the above-mentioned preparation device and includes the following steps: The inner cylinder wall surrounding the rotating shaft is caused to rotate around the rotating shaft to form a centrifugal state; Continuously spraying a first dispersion liquid and a second dispersion liquid on the surface of the inner cylinder wall to form a composite liquid layer, wherein the first dispersion liquid contains a first nano-carbon material, and the second dispersion liquid contains a second nano-carbon material, and the flow rate of the first dispersion liquid and / or the second dispersion liquid changes continuously over time, and the spraying area on the surface of the inner cylinder wall moves in a circumferential cycle due to the rotation of the inner cylinder wall; The composite liquid layer is continuously heated at a position other than the spraying area to volatilize the liquid dispersant, and the nano-carbon film is gradually thickened along the radial direction of the inner cylinder wall and has a gradient change in composition and / or structure as the inner cylinder wall rotates and assembles.

[0024] In some embodiments, the following steps may also be included: The nano-carbon film formed by the rotational assembly of the cylinder wall is heat-treated to change the component material of the nano-carbon film. The selected preparation route may be different for different materials. For example, for the gradient composite film of graphene and carbon nanotubes in the typical implementation case of the present invention, the obtained film needs to be subjected to high-temperature reduction annealing treatment so that the graphene oxide therein is reduced to graphene; of course, in some feasible implementation schemes, subsequent treatment may not be performed, and the desired composite film can be obtained after the rotation gradient spraying process is completed.

[0025] In some embodiments, the flow rate of the first dispersion liquid has a continuously decreasing trend, and the flow rate of the second dispersion liquid has a continuously increasing trend.

[0026] In some embodiments, during the complete assembly cycle of the nano-carbon film, the flow rate of the first dispersion liquid continuously decreases from an initial value to 0, and the flow rate of the second dispersion liquid continuously increases from 0 to an end value.

[0027] In some embodiments, the duration of the assembly cycle is 100-60000 min.

[0028] In some embodiments, the rotation speed of the inner cylinder wall is 500-3000 rpm.

[0029] In some embodiments, in the spraying area, the total spraying amount of the first dispersion and the second dispersion is 0.315 mL·min -1 If the spraying amount exceeds this value, the liquid film thickness may be too thick, which may cause the problem of liquid phase flow and cause certain damage to the gradient structure of the film layer.

[0030] In some embodiments, the first nano-carbon material is a nano-carbon material of two or more dimensions, and the second nano-carbon material is a one-dimensional or zero-dimensional nano-carbon material.

[0031] In some embodiments, the dispersion concentration of the nanocarbon material in the first dispersion and / or the second dispersion is 0.1-5 mg mL -1 .

[0032] Some other condition parameters, such as the power of the heater, can be appropriately set to basically ensure that the liquid layer is heated, dried during the continued rotation, and no longer has a flowable liquid phase when reaching the next round of spraying area.

[0033] As some typical examples of the above-mentioned technical solutions, the supercontinuous gradient composite film assembly device shown above can be used, using GO (graphene oxide) solution and SWNT (multi-walled carbon nanotube) dispersion, setting certain equipment parameters, and preparing a GO-SWNT film with a supercontinuous gradient structure. A high-temperature hot pressing furnace is used for high-temperature hot pressing reduction treatment, and a nanocarbon film with a continuous gradient pore structure is prepared by controlling the reduction process.

[0034] Furthermore, an embodiment of the present invention also provides a nano-carbon film obtained by the above preparation method, which comprises at least two nano-carbon materials, and the components and / or structure of the nano-carbon film present a continuous gradient change in the thickness direction.

[0035] In addition, the embodiments of the present invention also provide applications of the nano-carbon film in the fields of green electromagnetic shielding and Joule heat.

[0036] Correspondingly, an embodiment of the present invention further provides a green electromagnetic shielding material, characterized by comprising any of the aforementioned supercontinuous gradient structure nano-carbon composite films.

[0037] The technical solution of the present invention is further described in detail below through several embodiments and in conjunction with the accompanying drawings. However, the selected embodiments are only used to illustrate the present invention, and do not limit the scope of the present invention.

[0038] Example 1 This embodiment illustrates a preparation process of a nano-carbon film with a supercontinuous gradient, which is specifically as follows: Step 1: Synthesize GO using the Hummer method and dilute the GO dispersion to 2 mg mL -1 Set aside, the dispersing agent is water. Similarly, dilute the dispersed SWNT dispersion to 2 mg mL -1 Set aside, also as a water dispersion.

[0039] Step 2: Adjust the parameters of the continuous gradient assembly equipment: heating power 500 W, the speed change per minute of both peristaltic pumps was set to 0.525 μL min -1 , where the speed of GO dispersion was set to 0.315 mL min -1 to 0 mL min -1 , the speed of SWCNT dispersion was set to 0 mL min -1 to 0.315 mL min -1 , assembly time 600 minutes.

[0040] Step 3, the prepared GO dispersion and SWNT dispersion are placed in glass bottles respectively, and the solutions are injected using a peristaltic pump dedicated silicone tube, and the above parameters are used for controllable assembly of supercontinuous gradient GO-SWNT film.

[0041] Step 4, cut the GO-SWNT film prepared by the supercontinuous gradient assembly equipment into a suitable size, and then use a high-temperature hot pressing furnace to perform high-temperature hot pressing reduction treatment. The gas environment used is argon. The constant temperature treatment is carried out at 200°C for 1 hour to obtain a nanocarbon film with a continuous gradient pore structure.

[0042] For optical photos of the supercontinuous gradient nanocarbon film prepared in this example, please refer to Figure 2a and Figure 2b The two pictures show two different sides of the film. For SEM pictures of different sides of the surface film, see Figure 3a and Figure 3b As shown, the scanning electron microscope image of the entire cross section can be found in Figure 4a As shown, the high-magnification cross-sectional morphology at different positions along the thickness direction is shown in Figure 4b-4f As shown, according to these images, it can be seen that the nano-carbon film prepared in this embodiment has obvious characteristics of continuous changes in pore size and density in the thickness direction. These characteristics are the key structural features that bring excellent low-reflection electromagnetic shielding performance to the composite film.

[0043] The mechanical properties of the supercontinuous gradient nanocarbon film prepared in this embodiment were tested. For the data graph, please refer to Figure 5 In addition, please refer to the electromagnetic shielding performance data chart Figure 6a and Figure 6b As shown, and at different heat treatment temperatures, the electrical performance data can be found in Figure 7 As shown in these images, it can be seen that the supercontinuous gradient nanocarbon film has excellent mechanical properties, and the two sides of the film have different electrical properties and electromagnetic shielding properties.

[0044] Comparative Example 1 This comparative example is substantially the same as Example 1, except that: Instead of changing the flow rates of the two dispersions, the flow rates of the two dispersions were fixed at 0.158 mL min -1 , the total flow rate remains basically the same as that in Example 1, and other conditions remain unchanged.

[0045] Finally, the obtained composite film does not have gradient characteristics. Therefore, its film surface has a high electromagnetic wave reflectivity, which is not conducive to the absorption of electromagnetic waves inside the film.

[0046] Comparative Example 2 This comparative example is substantially the same as Example 1, except that: The nozzle is set at an upper position, and the spray direction is also vertically upward. The infrared heater used for heating is set at a lower position, which is generally opposite to the setting in Example 1.

[0047] Finally, the gradient characteristics of the obtained composite film are not obvious, the gradient structure is unstable, and the flow of liquid along the inner wall of the drum has a significant impact on the film assembly structure. It is difficult to achieve the controllable assembly of supercontinuous gradient nanocarbon films, and there are deficiencies in the application field of low-reflection electromagnetic shielding.

[0048] Comparative Example 3 This comparative example is substantially the same as Example 1, except that: The drum is no longer arranged horizontally, but the axis of rotation of the drum is perpendicular to the ground.

[0049] Finally, the gradient characteristics of the obtained composite film are not obvious, the gradient structure is unstable, and the flow of liquid from top to bottom has a significant impact on the film assembly structure. It is difficult to achieve the controllable assembly of supercontinuous gradient nanocarbon films, and there are deficiencies in the application field of low-reflection electromagnetic shielding.

[0050] Example 2 This embodiment illustrates a preparation process of a nano-carbon film with a supercontinuous gradient, which is specifically as follows: Step 1: Synthesize GO using the Hummer method and dilute the GO dispersion to 2 mg mL -1 The dispersed SWNT dispersion was diluted to 2 mg mL -1 spare.

[0051] Step 2: Adjust the parameters of the continuous gradient assembly equipment: heating power 45%, use a set of syringe pumps with large liquid output, and set the speed change per minute of the two peristaltic pumps to 0.525 μL min -1 , where the speed of GO dispersion was set to 0.315 mL min -1to 0 mL min -1 The speed of SWNT dispersion was set to 0 mL min -1 to 0.315 mL min -1 , assembly time 600 minutes.

[0052] Step 3: Place the prepared GO dispersion and SWNT dispersion in glass bottles respectively, use peristaltic pumps to inject the solutions by adjusting the injection speeds of the two peristaltic pumps, and use the above parameters to assemble the supercontinuous gradient GO-SWNT film.

[0053] Step 4, cut the GO-SWNT film prepared by the supercontinuum gradient assembly equipment into a suitable size and perform high-temperature hot pressing reduction treatment in a high-temperature hot pressing furnace. The gas environment used is argon. The temperature is kept constant at 2800°C for 1 hour to obtain a nanocarbon film with a supercontinuum gradient pore structure.

[0054] Example 3 This embodiment illustrates a preparation process of a nano-carbon film with a supercontinuous gradient, which is specifically as follows: Step 1: Synthesize GO using the Hummer method and dilute the GO dispersion to 2 mg mL -1 The dispersed SWNT dispersion was diluted to 2 mg mL -1 spare.

[0055] Step 2: Adjust the parameters of the continuous gradient assembly equipment: heating power 45%, use a set of syringe pumps with large liquid output, and set the speed change per minute of the two peristaltic pumps to 1.05 μL min -1 , where the speed of GO dispersion was set to 0.315 mL min -1 to 0 mL min -1 The speed of SWNT dispersion was set to 0 mL min -1 to 0.315 mL min -1 , assembly time 300 minutes.

[0056] Step 3: Place the prepared GO dispersion and SWNT dispersion in glass bottles respectively, use peristaltic pumps to inject the solutions by adjusting the injection speeds of the two peristaltic pumps, and use the above parameters to assemble the supercontinuous gradient GO-SWNT film.

[0057] Step 4, cut the GO-SWNT film prepared by the supercontinuum gradient assembly equipment into a suitable size and perform high-temperature hot pressing reduction treatment in a high-temperature hot pressing furnace. The gas environment used is argon. The temperature is kept constant at 2800°C for 1 hour to obtain a nanocarbon film with a supercontinuum gradient pore structure.

[0058] Example 4 This embodiment illustrates a preparation process of a nano-carbon film with a supercontinuous gradient, which is specifically as follows: Step 1: Synthesize GO using the Hummer method and dilute the GO dispersion to 4 mg mL -1 The dispersant is water, and 4 mg mL -1 The Fe3O4 dispersion was mixed with the GO dispersion in equal proportions to obtain 2 mg mL -1 Similarly, the dispersed SWNT dispersion was diluted to 2 mg mL -1 spare.

[0059] Step 2: Adjust the parameters of the continuous gradient assembly equipment: heating power 45%, use a set of syringe pumps with large liquid output, and set the speed change per minute of the two peristaltic pumps to 1.05 μL min -1 , where the rate of Fe3O4@GO dispersion was set to 0.315 mL min -1 to 0 mL min -1 The speed of SWNT dispersion was set to 0 mL min -1 to 0.315 mL min -1 , assembly time 300 minutes.

[0060] Step 3, the prepared Fe3O4@GO dispersion and SWNT dispersion are placed in glass bottles respectively, and a peristaltic pump is used to inject the solution by adjusting the injection speed of the two peristaltic pumps, and the above parameters are used to assemble the supercontinuous gradient Fe3O4@GO-SWNT film.

[0061] Step 4, the Fe3O4@GO-SWNT film prepared by the supercontinuum gradient assembly equipment is cut into a suitable size and subjected to high-temperature hot pressing reduction treatment in a high-temperature hot pressing furnace. The gas environment used is argon, and the temperature is kept constant at 1000°C for 1 hour to obtain a nanocarbon film with a supercontinuum gradient pore structure.

[0062] Example 5 This embodiment illustrates a preparation process of a nano-carbon film with a supercontinuous gradient, which is specifically as follows: Step 1: Synthesize GO using the Hummer method and dilute the GO dispersion to 4 mg mL -1 The dispersant is water, and 4 mg mL -1 The Fe3O4 dispersion was mixed with the GO dispersion in equal proportions to obtain 2 mg mL -1Similarly, the dispersed SWNT dispersion was diluted to 2 mg mL -1 spare.

[0063] Step 2: Adjust the parameters of the continuous gradient assembly equipment: heating power 45%, use a set of syringe pumps with large liquid output, and set the speed change per minute of the two peristaltic pumps to 1.05 μL min -1 , where the rate of Fe3O4@GO dispersion was set to 0.315 mL min -1 to 0 mL min -1 The speed of SWNT dispersion was set to 0 mL min -1 to 0.315 mL min -1 , assembly time 300 minutes.

[0064] Step 3, the prepared Fe3O4@GO dispersion and SWNT dispersion are placed in glass bottles respectively, and a peristaltic pump is used to inject the solution by adjusting the injection speed of the two peristaltic pumps, and the above parameters are used to assemble the supercontinuous gradient Fe3O4@GO-SWNT film.

[0065] Step 4, the Fe3O4@GO-SWNT film prepared by the supercontinuum gradient assembly equipment is cut into a suitable size and subjected to high-temperature hot pressing reduction treatment in a high-temperature hot pressing furnace. The gas environment used is argon, and the temperature is kept constant at 1000°C for 1 hour to obtain a nanocarbon film with a supercontinuum gradient pore structure.

[0066] Example 6 This embodiment illustrates a preparation process of a nano-carbon film with a supercontinuous gradient, which is specifically as follows: Step 1: Synthesize GO using the Hummer method and dilute the GO dispersion to 2 mg mL -1 Set aside, the dispersing agent is water. Similarly, dilute the dispersed SWNT dispersion to 2 mg mL -1 Set aside, also as a water dispersion.

[0067] Step 2: Adjust the parameters of the continuous gradient assembly equipment: heating power 500 W, the speed change per minute of both peristaltic pumps was set to 0.525 μL min -1 , where the speed of GO dispersion was set to 0.315 mL min -1 to 0 mL min -1 , the speed of SWCNT dispersion was set to 0 mL min -1 to 0.315 mL min -1 , assembly time 600 minutes.

[0068] Step 3, the prepared GO dispersion and SWNT dispersion are placed in glass bottles respectively, and the solutions are injected using a peristaltic pump dedicated silicone tube, and the above parameters are used for controllable assembly of supercontinuous gradient GO-SWNT film.

[0069] Step 4, cut the GO-SWNT film prepared by the supercontinuous gradient assembly equipment into a suitable size, and then use a high-temperature hot pressing furnace to perform high-temperature hot pressing reduction treatment. The gas environment used is argon. The constant temperature treatment is carried out at 200°C for 1 hour to obtain a nanocarbon film with a continuous gradient pore structure.

[0070] Step 5: Use the supercontinuous gradient RGO-SWNT film prepared above in the field of low-reflection electromagnetic shielding to test the total electromagnetic shielding effectiveness and the changes in the reflection and absorption values ​​of the electromagnetic waves when the electromagnetic waves are incident on both sides of the film. For the electromagnetic shielding performance data chart, please refer to Figure 6a and Figure 6b As shown in the figure, it can be seen that when the electromagnetic wave is incident on the RGO surface, the reflectivity of the electromagnetic wave is significantly lower than the reflectivity of the electromagnetic wave when it is incident on the SWNT surface, while the overall electromagnetic shielding effectiveness remains basically the same, indicating that the nanocarbon film can be used in the field of low-reflection electromagnetic shielding.

[0071] Based on the above embodiments and comparative examples, it can be clearly seen that the preparation device and method provided by the present invention prepare a new composite nano-carbon film with a supercontinuous gradient structure through gradient continuous coating combined with centrifugal casting. The device and method are simple to operate and have stable film formation, and can well realize the continuous gradient-controlled film formation of two-component nano-carbon materials. It provides a new preparation idea for the construction of multi-component continuous gradient composite film structures and provides support for the multifunctional application of supercontinuous gradient structure composite films.

[0072] The nanocarbon film with a continuous gradient pore structure prepared by the present invention has excellent electromagnetic shielding performance and low electromagnetic wave reflectivity. Its continuous gradient pore structure plays a vital role in the absorption of electromagnetic waves inside the material body, and provides a research basis for the development of nanocarbon materials in the field of green electromagnetic shielding.

[0073] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A device for preparing a nanocarbon film having a supercontinuum gradient structure, characterized in that: include: A first pump assembly, a second pump assembly, a spray assembly, a centrifugal assembly, and a heating assembly; The first pump assembly is used to pump a first dispersion to the spray assembly, and the second pump assembly is used to pump a second dispersion to the spray assembly, wherein the first dispersion contains a first nano-carbon material, and the second dispersion contains a second nano-carbon material, and the pumping rates of the first pump assembly and / or the second pump assembly can be changed continuously over time; The centrifugal component has a rotating shaft and an inner cylinder wall surrounding the rotating shaft, and can rotate with the rotating shaft as the rotating axis to generate centrifugal force. The spraying component can spray the first dispersion and the second dispersion onto the surface of the inner cylinder wall. The heating component is arranged in cooperation with the centrifugal component to heat the inner cylinder wall.

2. The preparation device according to claim 1, characterized in that: The spraying area of ​​the spraying component and the heating area of ​​the heating component are relatively arranged with the rotating shaft as the center point.

3. The preparation device according to claim 2, characterized in that: The rotating shaft is arranged non-parallel to the gravity direction, the spraying area is arranged at a relatively low position along the gravity direction, and the heating area is arranged at a relatively high position along the gravity direction.

4. The preparation device according to claim 3, characterized in that: The spraying assembly includes an injection nozzle connected to the first pump assembly and the second pump assembly, the injection nozzle extends into the enclosed space of the inner cylinder wall and points downward to the surface of the inner cylinder wall along the direction of gravity; The heating assembly includes an infrared heater, which extends into the enclosed space and is adjacent to a high area of ​​the inner cylinder wall.

5. A method for preparing a nanocarbon film having a supercontinuous gradient structure, characterized in that: include: The inner cylinder wall surrounding the rotating shaft is caused to rotate around the rotating shaft to form a centrifugal state; Continuously spraying a first dispersion liquid and a second dispersion liquid on the surface of the inner cylinder wall to form a composite liquid layer, wherein the first dispersion liquid contains a first nano-carbon material, and the second dispersion liquid contains a second nano-carbon material, and the flow rate of the first dispersion liquid and / or the second dispersion liquid changes continuously over time, and the spraying area on the surface of the inner cylinder wall moves in a circumferential cycle due to the rotation of the inner cylinder wall; The composite liquid layer is continuously heated at a position other than the spraying area to volatilize the liquid dispersant, and the nano-carbon film is gradually thickened along the radial direction of the inner cylinder wall and has a gradient change in composition and / or structure as the inner cylinder wall rotates and assembles.

6. The preparation method according to claim 5, characterized in that: Also includes: The nano-carbon film formed by the rotational assembly of the cylinder wall is heat-treated to change the component material of the nano-carbon film.

7. The preparation method according to claim 5, characterized in that: The flow rate of the first dispersion liquid has a trend of continuously decreasing, and the flow rate of the second dispersion liquid has a trend of continuously increasing.

8. The preparation method according to claim 7, characterized in that: The duration of the assembly cycle is 100-60000min; and / or, the rotation speed of the inner cylinder wall is 500-3000 rpm; And / or, in the spraying area, the total spraying amount of the first dispersion and the second dispersion is 0.315 mL·min -1 the following; And / or, the first nano-carbon material is a nano-carbon material of two dimensions or more, and the second nano-carbon material is a one-dimensional or zero-dimensional nano-carbon material; And / or, the dispersion concentration of the nanocarbon material in the first dispersion and / or the second dispersion is 0.1-5 mg mL -1 .

9. The nanocarbon film prepared by the preparation method according to any one of claims 5 to 8, characterized in that: The nano-carbon film comprises at least two nano-carbon materials, and the components and / or structures of the nano-carbon film show a continuous gradient change in the thickness direction.

10. Use of the nanocarbon film according to claim 9 in the field of low-reflection electromagnetic shielding or Joule heating.